Identification coral reef diatom using scanning electron microscope at Nature Reserve Pulau Sempu (NRPS), East Java - Sayyid Afdhal El Rahimi; Adryan Kryk; Sulastri Arsad; Oktiyas Muzaky Luthfi; Andik Isdianto; M. Azurea Bahri Luthfi (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
Diatom, Bacillariophyceae, has an important role in environmental support because these algae contribute to 25% of the oxygen supply globally and each year represent 40% of primary production by fixed carbon using photosynthesis. Diatom samples were obtained from 3 different sites in around NRPS. Cleaning diatoms analyzed using SEM for describe ultrastructure in diatom valves. Three dominant diatoms Cocconeidaceae and Bacillariaceae from the south Java Sea (Indian Ocean). Basic information regarding the diversity of diatoms, and the success of photoautotrophic micro-algae that can be found both in marine and freshwater habitats, is very important to describe the role of each taxon from an ecology perspective in the future. Samples are taken from the substrate of 3 stations in Nature Reserve Pulau Sempu and prepared in the laboratory for scanning electron microscopy photographs. Clear and detailed features diatom frustule of SEM photograph reveal a schild diatom (Cocconeis) and panduriform diatom (Psammodictyon) are dominating taxa in NRSP areas.Keywords:Hard coralCocconeisPsammodictyonPulau SempuDiatom